Valuing Heritage as a Public Good Initial Application to Zonal Travel Cost Method in Hoi An, Vietnam - Dung, Bui Dai; Thinh, Nguyen An; Ha, Nguyen Thi Vinh; Hanh, Nguyen Thi Hoa (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 3, 2019)
A literature overview shows that almost all of the valuation researches for heritage have built demand curves as for private goods. We argue that heritage is a high-end purity public good. A heritage valuation research would yield more accurate results if the demand curve could be built as that of a public good. This paper presents arguments for the superiority of the public good demand curve over that of private goods in the scope of heritage valuation, and initially applies the Zonal Travel Cost Method (ZTCM) in evaluating Hoi An, a World Heritage town in Central Vietnam, to look for evidence of such superiority. Evidence shows that: (i) The relationship between visits and travel cost could be represented more accurately by the public good’s demand curve rather than the private good’s curve; (ii) To build the demand curve for such a World Heritage site (tourists are inhomogeneous), it requires an additional technique to minimize potential distortions, in which the purchasing power parity ratio (PPP ratio) is used to adjust inconsistencies in actual traveling costs; (iii) The value of Hoi An, which is valued at 4,255,724,958 USD in accordance with its public good’s demand curve, shows that it is 206.6% higher than the value computed according to the private goods’ demand curve.